Soil Macrofauna Diversity in Organic and Conventional Vegetable Fields in Ternate City - Betty Kadir Lahati; Erwin Ladjinga (TECHNO: JURNAL PENELITIAN, 2021)
This research is a descriptive exploratory study aiming at analyzing the abundance index and diversity index of soil macrofauna in organic and conventional vegetable fields.  The research method used is an entrapment (Pitfall traps) method where traps are installed in a land with 10mx25m of size and results in 10 plots. Each plot has 5 points determined diagonally to place the pitfall traps; therefore, the total sample points are 50 samples per observation location. Identification of macrofauna trapped in the pitfall trap uses a microscope. Based on the results of diversity analysis, soil macrofauna in organic fields has H'2.6546 with an abundance of 2242 individuals, whereas the conventional fields have H'1.6775 with an abundance of 1507 individuals. In terms of dominance index, the conventional fields have a higher evenness of 0225 with a low value of 0229, while the organic fields have a low dominance index of 0077 yet a higher evenness value of 0344. It can be concluded that the diversity of soil macrofauna in the organic vegetable fields in Ternate city has a higher diversity value because the fields have abundant and more even availability of soil macrofauna so that there are no dominant species found. On the other hand, the conventional vegetable fields have low abundance so that the diversity of soil macrofauna in the fields is low due to one dominant species. The results of the analysis in the two fields indicate that the similarity index is 0.803, which means that the similarity value of the macrofauna species in the two fields is close to the index value. An index value is 0 if there are no similar species in both fields and the value is 1 when both fields have the same species composition. However, the diversity of soil macrofauna in the two different fields has an abundance of soil macrofauna so that it can increase soil fertility and maintain the stability of soil macrofauna and its function in a sustainable agricultural system.